Management of Skeletal Class-II Malocclusion Using Advansync 2: A Case Series (Medico Legal Update, 2020)
Angle’s class II division 1 malocclusion, being the most commonly occuring type of malocclusion, ischallenging to treat especially when there is an underlying skeletal discrepancy. Various fixed functionalappliances have been developed over the years by different authors for correction of skeletal class IImalocclusion due to retrognathic mandible. Among the fixed functional appliances available for class IIcorrection, Advansync2 (Ormco Co, Glendora, Calif) also known as molar to molar appliance has been usedeffectively in the recent past. It is a fixed tooth-born functional appliance with an advantage of allowingconcurrent use of fixed orthodontic therapy. This facilitates reduction of the overall treatment duration. Twocase reports of patients treated using the Advansync2 class II corrector has been presented along with theskeletal and dentoalveolar changes observed during the treatment. The effects observed were similar to mostfixed functional appliances however the treatment duration was considerably reduced in all the cases.